Design of Clean Water Booster Pump for High-Rise Buildings - Luh Putu Ike Midiani; I Made Duta Irawan; Ketut Bangse; I Nyoman Gunung (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
A sanitary system is a supporting component designed to meet the clean water requirements of a building, primarily for sanitation activities. The average sanitary equipment used typically requires a shower pressure of ±1 Bar. However, the shower pressure can be significantly affected by factors such as the distance from the top tank and the building's layout, considering only the pressure due to gravity. To address inadequate shower pressure, an auxiliary pump known as a booster pump is necessary. The need for a booster pump is determined by the cumulative demand from plumbing equipment, where the total capacity required is 6057 liters/hour. To address this demand, the system employs two pump units, each with a capacity of 3 m3/hour. The distribution pipes utilized in the system adhere to established standards and are made of random polypropylene with a diameter of 2 inches and a flow rate of 0.005889 m3/second. The overall head loss resulting from this installation amounts to 31.62 meters. To accommodate the booster system, a pressure tank with a capacity of 67 liters is employed. The minimum working pressure required for the pumps is 1.8 Bar.